Напрацювання ключових механізмів забезпечення якості загальної середньої освіти у Фінляндії (другa пол. ХХ ст.) - Волинець, Людмила (Studies in Comparative Education, 2014)
Статтю присвячено аналізу напрацювання ідей, політичних принципів, що у процесі реформування освіти Фінляндії упродовж другої половини ХХ ст., як ключових механізмів сучасної системи забезпечення якості загальної середньої освіти країни. Йдеться зокрема про такі ключові механізми як загальнонаціональне усвідомлення ролі освіти як вирішального чинника успішного соціального та економічного розвитку країни; увага до визначення і виконання цілей освіти; соціальна справедливість та рівні освітні можливостей; стійке політичне керівництво і стабільний розвиток системи освіти відповідно до визначених стратегічних цілей; якісна підготовка вчителя; збалансованість центрального й місцевого рівнів управління освітою; гнучкий підхід до стандартизації; партнерський характер стосунків усіх учасників освітнього процесу тощо. Статья посвящена анализу наработки идей, политических принципов и т.п. в процессе реформирования образования в Финляндии во второй половине ХХ века, как ключевых механизмов современной системы обеспечения качества общего среднего образования страны. В часности, речь идеь о таких ключевых механизмах как общенациональное осознание роли образования как решающего фактора успешного социального и экономического развития страны; внимание к определению и выполнению целей образования; социальная справедливость и равные образовательные возможности; устойчивое политическое руководство и стабильное развитие системы образования в соответствии с определенными стратегическими целями; качественная подготовка учителей; сбалансированность центрального и местного уровней управления образованием; гибкий подход к стандартизации; партнерский характер отношений всех участников образовательного процесса и др. The article is dedicated to the analysis of development of ideas, political principles, etc. in the process of Finnish education reformation during the second half of the 20th century. These ideas, principles, etc. are key mechanisms of modern system of ensuring secondary education quality in the country. In particular, the author pays attention to the fact that consistent political leadership and educational system development in accordance with defined strategic objectives was achieved due to two factors. First of all, this involves national awareness (beginning from the end of World War II) of the role of education as a key factor of successful social and economic development Secondly, this concerns the understanding of the vital need of educated and competent citizens, namely human capital. The understanding of the need of careful identification and implementation of core educational values and goals, as well as careful research, analysis, and review of national education elements by Finnish teachers and politicians, became important mechanisms of ensuring secondary education quality. The creation and support of social justice of secondary education system providing equal educational opportunities for all students enabled high level of citizens’ trust towards Finnish educational system. Rethinking of knowledge concepts in the light of discoveries in pedagogics related sciences (cognitive psychology, constructivist theories, neuroscience, etc.); extremely responsible attitude to the selection and training of teaching staff; replacing burdensome reporting with teachers’ responsibility for what and how they teach; and scientific and research activities of school heads and teachers have also become key mechanisms of ensuring the quality of secondary education in Finland. Balance between the central and local levels of education governance allowed to realize a flexible approach to standardization, thus enabling creative implementation of National Curriculum locally. Participatory nature of the relationships between all educational process’ participants (teachers, students, parents, schools, and other public institutions) helped to transform competitiveness and accountability into joint public responsibility for improving Finnish schools.